Buckling of lipidic ultrasound contrast agents under quasi-static load. (3rd April 2023) - Chabouh, Georges; van Elburg, Benjamin; Versluis, Michel; Segers, Tim; Quilliet, Catherine; Coupier, Gwennou
Abstract : Collapse of lipidic ultrasound contrast agents under high-frequency compressive load has been historically interpreted by the vanishing of surface tension. By contrast, buckling of elastic shells is known to occur when costly compressible stress is released through bending. Through quasi-static compression experiments on lipidic shells, we analyse the buckling events in the framework of classical elastic buckling theory and deduce the mechanical characteristics of these shells. They are then compared with that obtained through acoustic characterization. This article is part of the theme issue 'Probing and dynamics of shock sensitive shells'.